Some aspects of the teaching of reading in the primary grades in some selected public schools in the Philippines and implication for Iran - Ehteshami, Iran 1922- (s.n.], 1965)
This study determines the effective methods of teaching reading in the primary schools of the Philippines and the factors causing the slow or non-learning of reading in the primary level. From the findings, the investigator has deduced implications for the methods of teaching reading in Iran.